2018
DOI: 10.1177/1747954118761202
|View full text |Cite
|
Sign up to set email alerts
|

Ecological dynamics of spin bowling in test match cricket: A longitudinal analysis of delivery speed between Australia and India

Abstract: The purpose of this study was to highlight the effects of the environment on spin bowling tactics in test match cricket. The speed differences employed by Indian and Australian spin bowlers in home and away test matches were examined over a nine-year period. Eleven test matches played in Australia and 10 test matches played in India from 2007 to 2015 were analysed (3413 spin overs). During this time, 12 spin bowlers represented Australia (mean age 28.0 ± 3.7 years) and 13 represented India (mean age 29.1 ± 4.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Previous longitudinal studies in other sports such as football, 3,4,[17][18][19] cricket 20 or Australian football 21 have shown how patterns of team structure and play evolve over time. The long-term trends found can be used to better understand how sports will likely continue to change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies in other sports such as football, 3,4,[17][18][19] cricket 20 or Australian football 21 have shown how patterns of team structure and play evolve over time. The long-term trends found can be used to better understand how sports will likely continue to change.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, a recent study examined the difference in spin bowling delivery speed during test matches played between Australia and India from 2007 to 2015 in both Australian and Indian environments. 25 It was reported that the success of Australia's spin bowlers in their home environment was linked with a lower bowling average and bowling strike rate compared to Indian spin bowlers. There was also less variability in the delivery speed of Australian spin bowlers in 9 of the 11 matches (ratio < 0.83).…”
Section: Discussionmentioning
confidence: 99%
“…10,20,21,27,31,[33][34][35][36][37] The remaining six studies investigated the effect of pitch type on bowling performance. [22][23][24][25]32,38 The summary of findings of the included studies has been provided in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For example, a tennis player who is brought up in a talent development program on clay courts is more likely to become a strong baseline player, whereas one brought up on grass courts, would more likely develop a strong serve and volley game as the affordances of these surfaces invite the player to develop these skills 51 . A cricket spin bowler who is brought up in Australia on hard pitches where the ball has lots of bounce, will typically bowl faster and with less variability in delivery speed than those spin bowlers brought up on pitches in the Indian sub-continent 52 . These experiences result in bowlers performing better in the environments to which they are most adapted or attuned to, based on their development 52 .…”
Section: Ecological Dynamics and Skill Adaptationmentioning
confidence: 99%
“…A cricket spin bowler who is brought up in Australia on hard pitches where the ball has lots of bounce, will typically bowl faster and with less variability in delivery speed than those spin bowlers brought up on pitches in the Indian sub-continent 52 . These experiences result in bowlers performing better in the environments to which they are most adapted or attuned to, based on their development 52 .…”
Section: Ecological Dynamics and Skill Adaptationmentioning
confidence: 99%